Prevalence and pattern of ocular morbidity and factors influencing ocular morbidity in a rural population in south India: a community based cross sectional study - ., Venkataramana; R. L. C., Amarnath (International Journal Of Community Medicine And Public Health, 2017)
Background: Preventable blindness is still one of the major public health problems in India. The scarcity of community-based studies on ocular morbidity, more especially from rural areas is one of the reasons for the inadequate focus on the subject. The objectives were to study the pattern and factors associated with ocular morbidity in a rural adult population. Methods: The study was a cross sectional study conducted in field practice area of rural health Center, Cheluvanatti village in the state of Karnataka. Among 16 villages, one village was selected by convenient sampling. Ocular morbidity was assessed by detailed history and clinical examination by trained clinicians. Results: Among total 1181 population, 872 people >18 years were included in the final analysis. Majority portion (72.9%) of the study population was in 18-45 years age group. There were 51.3% of males and the proportion of females was 48.7%. The prevalence of ocular morbidity was 13.9% (95% CI 12.0%-16.0%) in the study population. The most common ocular morbidity was refractive errors seen in 56(6.4%), followed by cataract seen in 35 (4%) and corneal blindness seen in 26 (3%) subjects. The presence of ocular morbidity was 4.49 times more in 46-60 years age group compared with 18 to 45 years age group (95% CI 2.76 -7.33, p<0.01). Compared with higher studies people the presence of ocular morbidity in illiterate was 35.32 times more (95% CI 16.61-75.12, p<0.01). The presence of ocular morbidity was 20.64 times more in diabetic patients (95% CI 8.95-47.61, p<0.01) comparing with non-diabetic patients. Conclusions: The prevalence of ocular morbidity is still more in aged people and the village people are getting more effect with their practices and behavior. There is a need to go with more community-based cross sectional studies and also the preventive methods to reduce and avoid the risk of ocular diseases.